Avaliação de mediadores da resposta inflamatória em gestantes diabéticas - Gueuvoghlanian-Silva, Bárbara Yasmin [UNIFESP] (2010)
Background: Adiponectin is involved in glycemic regulation and in the physiopathology of obesity. Adiponectin gene polymorphisms may influence the expression of this molecule. The aims of this study were to assess adiponectin +45 (rs2241766) and -11377 (rs266729) gene polymorphisms and adiponectin serum levels in Brazilian women with gestational diabetes (GD) according to the patients´ prepregnancy body mass index (BMI). Methods: This case-control study involved 79 GD patients and 169 healthy pregnant controls (C) grouped according to BMI (normal < 25 and obese ≥ 25). Genomic DNA was extracted from peripheral blood, and polymorphisms genotyping were obtained by digesting PCR products with the following restriction endonucleases: SmaI (+45) and HhaI (-11377). Adiponectin serum levels were determined by ELISA. Data were analyzed by Mann-Whitney, chi-square or Fisher tests; p<0.05 was considered significant. Results: When both groups were analyzed, adiponectin serum levels were higher in C than in GD women (p=0.0004). Adiponectin serum levels were higher in normal weight versus obese women, both in the C (p=0.01) and in GD (p=0.03) groups, as well as in normal weight C versus normal weight GD (p=0.03) and in obese C compared to obese GD women (p=0.01). Conclusions: Our data suggest that there were no associations between GD and the analyzed gene polymorphisms. There was a significant association between adiponectin -11377 gene polymorphism and adiponectin levels in healthy pregnant women. GD women have decreased adiponectin levels independently of BMI.